Modification of adhesive bridge design to improve retention and good cleansing effect on loss of mandibular molars Kennedy Class III - Muhsin; Sani Wijaya; Setyawan Bonifacius; Rasmi Rikmasari (Indonesian Journal of Prosthodontic, 2023)
Fixed partial denture is preferred because it provides better comfort than removable dentures. Conventional FPD requires a lot of abutment preparation, and not all patients can perform this procedure. Adhesive bridges allow mi-nimal tooth preparation with design modifications to increase retention and a good cleansing effect to avoid secon-dary caries. The purpose of this article is to provide an overview of the modified adhesive bridge design on missing mandibular molars to enhance retention and good cleansing effect. A 29-year-old male came to the Dental and Oral Hospital Unpad with desire to have FD made. Patient lost first molar mandibular after tooth extraction about 10 months ago and doesn’t desire excessive tooth reduction. The treatment was an adhesive bridge on tooth 46 with sanitary pontic design, metal mesh, metal wings on teeth 47 and 45, occlusal rest on mesial and distal 47 and distal 45. Retention obtained was in the form of mechanical, chemical, and combination retention. It is concluded that adhesive bridge with sanitary pontic is appropriate treatment option for loss of one mandibular molar. Minimal pre-paration of healthy teeth and better self-cleaning effect are the advantages of this treatment.